Volume 3: Multiagent Network Systems; Natural Gas and Heat Exchangers; Path Planning and Motion Control; Powertrain Systems; Re 2015
DOI: 10.1115/dscc2015-9757
|View full text |Cite
|
Sign up to set email alerts
|

A Sequential Two-Step Algorithm for Fast Generation of Vehicle Racing Trajectories

Abstract: The problem of maneuvering a vehicle through a race course in minimum time requires computation of both longitudinal (brake and throttle) and lateral (steering wheel) control inputs. Unfortunately, solving the resulting nonlinear optimal control problem is typically computationally expensive and infeasible for real-time trajectory planning. This paper presents an iterative algorithm that divides the path generation task into two sequential subproblems that are significantly easier to solve. Given an initial pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 13 publications
0
27
0
Order By: Relevance
“…The goal of the above minimum time optimal control problem is to steer the dubins car from the starting state x S to the terminal point x F , while satisfying input saturation constraints and avoiding an obstacle. The obstacle is represented by an ellipse centered at (x obs , y obs ) = (27, −1) with semiaxis (a x , a y ) = (8,6). At iteration 0, we compute a first feasible trajectory using a brute force algorithms and we use the closed-loop data to initialize the LMPC (12) and (14) with N = 6.…”
Section: A Minimum Time Obstacle Avoidancementioning
confidence: 99%
“…The goal of the above minimum time optimal control problem is to steer the dubins car from the starting state x S to the terminal point x F , while satisfying input saturation constraints and avoiding an obstacle. The obstacle is represented by an ellipse centered at (x obs , y obs ) = (27, −1) with semiaxis (a x , a y ) = (8,6). At iteration 0, we compute a first feasible trajectory using a brute force algorithms and we use the closed-loop data to initialize the LMPC (12) and (14) with N = 6.…”
Section: A Minimum Time Obstacle Avoidancementioning
confidence: 99%
“…While using nonlinear optimization to find the optimal trajectory for a full circuit is computationally expensive, Timings and Cole showed that convex optimization can be used to reduce the required computation time for these problems [8]. Kapania et al achieved further reduction in computation time by using alternating convex subproblems to find approximately optimal trajectories [9]. This approach was experimentally validated by testing on an autonomous vehicle as was the receding horizon approach of Gerdts et al [10].…”
Section: A Related Workmentioning
confidence: 99%
“…Through the use of nonlinear programming, Perantoni et al [14] computes the time-optimal speed profile and racing line for an entire race track, although computational limitations require the trajectories to be computed offline. Kapania and Gerdes [15] presents an experimentally validated algorithm that reduces computational expense by breaking down the combined lateral/longitudinal vehicle control problem into two sequential subproblems that are solved iteratively.…”
Section: Related Workmentioning
confidence: 99%